Childhood tuberculosis: A roadmap towards zero deaths. (13th June 2014) - Marais, Ben J; Graham, Stephen M
Abstract: 'Every day, more than 200 children under the age of 15 die needlessly from tuberculosis (TB) – a disease that is preventable and curable. The World Health Organization estimates that as many as 1 in 10 TB cases globally (6–10% of all TB cases) are among this age group, but the number could be even higher because many children are simply undiagnosed.' Childhood TB is emerging from the shadows. This quote comes from the recently launched international roadmap towards zero TB deaths in children. We provide a brief update of new developments and remaining challenges related to childhood TB, with particular emphasis on the new roadmap.